Description of longitudinal tumor evolution in a case of multiply relapsed clear cell sarcoma of the kidney. Issue 2 (29th December 2021) - Yaguchi, Tomoki; Kimura, Shunsuke; Sekiguchi, Masahiro; Kubota, Yasuo; Seki, Masafumi; Yoshida, Kenichi; Shiraishi, Yuichi; Kataoka, Keisuke; Fujii, Yoichi; Watanabe, Kentaro; Hiwatari, Mitsuteru; Miyano, Satoru; et al.
Abstract: Background: Clear cell sarcoma of the kidney (CCSK) is the second most common pediatric renal tumor. Case: A 2‐year‐old boy was diagnosed with CCSK, which relapsed four times until he yielded to the disease at the age of 7 years. To characterize the longitudinal genetic alterations occurring in the present case, we performed targeted‐capture sequencing by pediatric solid tumors panel (381 genes) for longitudinally sampled tumors, including autopsy samples of metastasis. Internal tandem duplication of BCOR ( BCOR ‐ITD) was the only truncal mutation, confirming the previously reported role of BCOR ‐ITD in CCSK. Conclusion: Acquisition of additional mutations along tumor relapses and detection of metastasis‐specific mutations were reminiscent of the tumor progression and therapeutic resistance of this case, leading to clonal selection and a dismal fate.